Emphysematous Cystitis: Report of an Atypical Case. (24th October 2011) - De Baets, Karen; Baert, Joost; Coene, Luc; Claessens, Marc; Hente, Robert; Tailly, Geert
Abstract : We report the atypical case of a nondiabetic 66-year old male with severe abdominal pain and vomiting who was found to have emphysematous cystitis. Of all gas-forming infections of the urinary tract emphysematous cystitis is the most common and the least severe. The major risk factors are diabetes mellitus and urinary tract obstruction. Most frequent causative pathogens are Escherichia coli and Klebsiella pneumoniae . The clinical presentation is nonspecific and ranges from asymptomatic urinary tract infection to urosepsis and septic shock. The diagnosis is made by abdominal imaging. Treatment consists of broad-spectrum antibiotics, bladder drainage, and management of the risk factors. Surgery is reserved for severe cases. Overall mortality rate of emphysematous cystitis is 7%. Immediate diagnosis and treatment is necessary because of the rapid progression to bladder necrosis, emphysematous pyelonephritis, urosepsis, and possibly fatal evolution.